Proposals to reduce black carbon emissions for mobile sources in Costa Rica - Alvarado-Jiménez, Daniela (2022)
[Introduction]: Mobile sources, both globally and nationally, play a critical role in the generation of black carbon emissions, a short-lived climate forcer that has a great impact on the climate. [Objective]: Solutions are proposed that allow the mitigation of black carbon emissions generated by the transport sector within a framework of economic and technical feasibility. [Methodology]: The emissions generated by mobile sources were modeled, taking 2016 as the base year, for which the Copert 5.2 software was used. Subsequently, scenarios of reduction opportunities were established, which were evaluated considering their reduction potential, the concordance with public policies and the cost of the technology. [Results]: Mobile sources emitted 471.9 tons of black carbon into the atmosphere during 2016, which is equivalent to 217 031.7 and 707 712.2 tons of CO2e (taking 460 and 1 500 as global warming potential, respectively). It is proposed: the use of low-emission fuels, the incorporation of electric vehicles and technological improvements in the engine system to reduce exhaust emissions. [Conclusions]: The most feasible emission mitigation measures are those related to the incorporation of low-emission fuels, such as biodiesel and low-sulfur diesel. It is vitally important to include concrete actions for the reduction of black carbon emissions within national climate change policies, since their reduction has positive impacts in the short term.